Effect of HCl treatment on physico-chemical properties and photocatalytic performance of Fe–TiO2 nanotubes for hexavalent chromium reduction and dye degradation under visible light. (December 2021) - Zafar, Zulakha; Fatima, Rida; Kim, Jong-Oh
Abstract: In this study, we prepared Fe2 O3 /TNT composite (Fe-TNT) foil by combining anodization with the hydrothermal method. Photocatalytic reaction was restricted by a cluster of iron particles accumulated on the foil surface and the photocatalytic reaction sites reduces. Herein, using XPS determined that these iron particles are composed of iron oxide. An acid treatment, hydrochloric acid (HCl) was used to successfully remove the surface accumulation of iron oxide particles on the photocatalyst. Using cleaned Fe-TNT foil, the photocatalytic activity of 5 mg/L Congo red (CR) and hexavalent chromium reduction was significantly increased under visible irradiation. In addition, the influence of different aspects such as pH, the concentration of Fe, and the effect of different acid treatment time was evaluated. Removing the surface accumulated iron oxide and adjusting the pH in acidic medium, 73% hexavalent chromium reduction achieved within 180 min. The reusability was also explored by monotonous CR degradation. The CR degradation using Fe0.25 -TNT was lessened from 78% in the first cycle to 71% in the 3rd cycle. It was also confirmed experimentally that photocatalytic activity improvement of HCl treated Fe-TNT was not due to alternation in nanotube structure. Highlights: HCl was used to remove the cluster of iron oxide from the nanotubes surface to improve its efficiency. HCl treated Fe-TNT exhibited improved photocatalytic performance for CR degradation and reduction of Cr(VI) as well. Improved removal efficiency can be attributed to the removal of surface iron oxide. Higher acid treatment time reduced the photocatalytic activity because acid removed iron from the crystal lattice also.